Inoculating plant growth-promoting bacteria and arbuscular mycorrhiza fungi modulates rhizosphere acid phosphatase and nodulation activities and enhance the productivity of soybean (Glycine max) - Ngosong, Christopher; Tatah, Blaise Nangsingnyuy; Olougou, Marie Noela Enyoe; Suh, Christopher; Nkongho, Raymond Ndip; Ngone, Mercy Abwe; Achiri, Denis Tange; Tchakounté, Gylaine Vanissa Tchuisseu; Ruppel, Silke (Frontiers in Plant Science, 2022)
The cultivation of soybean (Glycine max) is important for its dual role as a rich source of dietary protein and soil fertility enhancer, but soybean production in Cameroon is constrained by soil infertility. This is often resolved using chemical fertilizers that exert deleterious effects on the environment when applied in excess. This field study was conducted at Nkolbisson-Yaoundé in the agro-ecological zone five of Cameroon, to assess the effect of inoculating plant growth-promoting bacteria (PGPB) and Arbuscular mycorrhiza fungi (AMF) on the performance of soybean, with or without the addition of NPK fertilizers. Ten treatments (Control–no input, PGPB, AMF, PGPB+AMF, PGPB+N, PGPB+PK, PGPB+N+PK, PGPB+AMF+N, PGPB+AMF+PK, and PGPB+AMF+N+PK) were established in a randomized complete block design with three replicates. Root colonization by AMF occurred only in soybean plants that received mycorrhiza inoculum. Inoculating PGPB and AMF enhanced root nodulation and acid phosphatase activities in the rhizosphere of soybean without NPK addition (P<0.001). The number of effective root nodules correlated positively (r=0.67, P<0.001) with acid phosphatase activity in the rhizosphere. Inoculating PGPB and AMF increased soybean yield and grain contents of carbohydrate, protein, zinc, and iron, especially when the microbes were integrated with NPK (P<0.001). The positive correlation between soybean grain yield and acid phosphatase activity (r=0.63, P<0.001) or the number of effective root nodules (r=0.66, P<0.001) reflect the rhizosphere microbe-mediated mechanisms by which the inoculated beneficial microbes exerted influence on the soybean yield and biofortification of grains. Thereby, highlighting the importance of inoculating beneficial microbes as a sustainable soil fertility management strategy to enhance biotic interactions in the rhizosphere, and to improve the performance of soybean.